Use of Coffee Husk Ash in the Stabilization of Sandy Soils for Subgrade Formation on Flexible Pavements - Ronet Ankwatsa (Uganda Christian University, 2025)
This report provides a detailed study on the use of coffee husk ash (CHA) as a sustainable sand soil stabilizer for subgrade formation on a flexible pavement along Mboghoyabo road in Kasese municipality. This region is associated with high levels of road instability due to the presence of the underlying sandy soils that experience erosion and settlement especially during the rainy season. The major methods used in the study included laboratory tests to determine the engineering properties of the soils and the chemical properties of the coffee husk ash. The results from the tests conducted showed significant improvements in the engineering properties, with CBR having the highest percentage increase of 166%, 91%, 23%, 41%, 40%, 37%, and 91% increases in the PI, linear shrinkage, OMC, MDD, CBR swell and UCS respectively. 10% CHA addition was found to be the optimum content that gave more significant improvements.
Undergraduate